Firm Level Decisions and Human Resource Development in an Islamic Economy - Abdul Aziz (International Institute of Islamic Thought, 1993)
Japan and Germany were totally destroyed during the Second World War. Their industrial complexes lay in ruins after the devastating Allied air bombardments. Both countries emerged from the war under Allied occupation and with almost all of their manufacturing facilities and infrastructures, such as transportation and telecommunications, paralyzed. A picture of war-ravaged Japan appeared in the Nippon Times of 23 September 1946: In Tokyo, 70 percent of the area of the city was destroyed, in Osaka 80, in Nagoya 90. Transportation was limited to crowded, creaky trains, hand-pulled two-wheel 'rear cam' designed to be attached to bicycles and ox carts. At war's end, in all of Japan there were only 41,000 motor vehicles, half of them inoperable and almost all the rest powered by charcoal fumes. There were no street lights at night and very few house lights. Germany's infrastructure suffered a similar fate: The condition of Germany at the end of World War II was desperate. The country seemed to be one vast rubble dump. The economy was in ruins; factories, railroads, ports, and canals had been destroyed; and many millions had-lost their homes. Many ...